Behavioral symptoms related to cognitive impairment - Dillon, Carol (2013)
Neuropsychiatric symptoms (NPS) are core features of Alzheimer's disease and related dementias. On one hand, behavioral symptoms in patients with mild cognitive impairment (MCI) can indicate an increased risk of progressing to dementia. On the other hand, mild behavioral impairment (MBI) in patients who usually have normal cognition indicates an increased risk of developing dementia. Whatever the cause, all dementias carry a high rate of NPI. These symptoms can be observed at any stage of the disease, may fluctuate over its course, are a leading cause of stress and overload for caregivers, and increase rates of hospitalization and early institutionalization for patients with dementia. The clinician should be able to promptly recognize NPI through the use of instruments capable of measuring their frequency and severity to support diagnosis, and to help monitor the treatment of behavioral symptoms. The aims of this review are to describe and update the construct 'MBI' and to revise the reported NPS related to prodromal stages of dementia (MCI and MBI) and dementia stages of Alzheimer's disease and frontotemporal lobar degeneration.